Diagnosis and Treatment of ADHD: NIH Consensus Report - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The following is a synopsis of the consensus statement issued by the planning committee and panel members of a conference on ADHD held at the NIH, November 16-18, 1998.